Water surface area and temperature change detection analysis in lagoons (a case study in puttalam lagoon, puttalam) - Hicmathullah, M.L.M.; Nafla, A.W.F.; Nanthakumaran, A. (university of Jaffna, 2020)
Puttalam lagoon significantly contributes for the livelihood through fishing for the economically deprived community in Puttalam District, Sri Lanka. Observable anthropogenic activities and rapid urban development cause deterioration of water quality and reduction of surface area of water body. The objective is to study the spatiotemporal changes on the surface area and on surface temperature of lagoon. This study was done using geographic information system and remote sensing approach for the six Landsat (3 TM, 1 ETM and 2 OLI) imageries and Water Ratio Index was applied to extract and quantify the changes in the surface area and spectral radiance approaches to determine the land surface temperature of the lagoon for the period of 1988, 1995, 2001, 2008, 2015 and 2019. The multi temporal map of surface area and surface temperature maps were produced for the change directions. The results revealed a significant decrease in surface area of the lagoon which was nearly 8.7% of its surface area and an increase of temperature by nearly 5.2oC during the period of study. Strong negative correlation (Pearson's correlation coefficient = 0.91) observed at 95% of significance level (p value = 0.01) between the surface area and temperature of lagoon. It is essential to take conservation measures to sustain this lagoon at Puttalam.
Keywords: Remote sensing; Change detection; Land surface temperature; Water ratio index; Geographic information system